2008
DOI: 10.1002/ange.200803526
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the PEG Mucoadhesivity Paradox to Engineer Nanoparticles that “Slip” through the Human Mucus Barrier

Abstract: Mucus linings serve as the bodys first line of defense at exposed surfaces of the eye and respiratory, gastrointestinal, and cervicovaginal tracts. The high viscoelasticity and adhesivity of mucus traps and limits exposure to foreign pathogens, [1, 2] toxins, [3] and environmental ultrafine particles, [1,4] which are all typically removed by normal mucus clearance mechanisms. Numerous studies have demonstrated that human mucus also strongly immobilizes conventional synthetic nanoparticles, [5][6][7] and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 32 publications
6
59
0
Order By: Relevance
“…All of these observations are553 in line with previous results described by Wang and co-workers 554 who described that 200 nm poly(styrene) particles coated with 555 either 5 kDa-PEG diffused in vitro as rapidly through mucus as 556 those with 2 kDa PEG, but a further increase of PEG MW to557 10 kDa resulted in 1000-fold slower transport in human cervico 558 vaginal mucus[19]. In fact the 10 kDa PEG chains may be long 559 enough to significantly entangle with mucins [37].Another important factor that appears to modulate the mucuspermeating properties of PEG-coated nanoparticles is the extent of 562 the PEG surface coverage.…”
supporting
confidence: 92%
“…All of these observations are553 in line with previous results described by Wang and co-workers 554 who described that 200 nm poly(styrene) particles coated with 555 either 5 kDa-PEG diffused in vitro as rapidly through mucus as 556 those with 2 kDa PEG, but a further increase of PEG MW to557 10 kDa resulted in 1000-fold slower transport in human cervico 558 vaginal mucus[19]. In fact the 10 kDa PEG chains may be long 559 enough to significantly entangle with mucins [37].Another important factor that appears to modulate the mucuspermeating properties of PEG-coated nanoparticles is the extent of 562 the PEG surface coverage.…”
supporting
confidence: 92%
“…The use of PEG with adequate MW is essential in order to achieve sufficient surface coating while avoiding the presence of long polymer chains that could promote adhesion by interpenetration mechanisms with mucin fibers. Values of 2-5 kDa were shown ideal for enhanced diffusive behavior, while longer PEG chains (10 kDa) were able to delay the transport of 200 nm PS NPs in cervicovaginal mucus as determined using MPT [75]. Similar results were obtained by Cu and Saltzman [76] for the transport of PEG-modified PLGA NPs in cervical mucus, as assessed by fluorescent microscopy and using a mass transport mathematical model, except for 10 kDa PEG-modified particles.…”
Section: Accepted Manuscriptsupporting
confidence: 73%
“…Hydrogen bonding or Van der Waals interactions are other types of interactions which can also contribute to the ion-pairing process [2][3][4]. Apart from nanoparticles with a densely charged, yet net neutral surface, an uncharged nanoparticle may be also considered as mucoinert as viral capsids, provided it is sufficiently hydrophilic with a low hydrogen bonding http capability (e.g., polyethylene glycol (PEG), cyclodextrin coatings) [1,5]. Wang et al [5] covalently modified the surfaces of polystyrene nanoparticles with CH 3 O-PEG-NH 2 of various molecular weights (MW = 2, 5, 10 kDa) and showed that low PEG MW and high PEG surface coverage are both required for rapid mucus penetration of coated NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from nanoparticles with a densely charged, yet net neutral surface, an uncharged nanoparticle may be also considered as mucoinert as viral capsids, provided it is sufficiently hydrophilic with a low hydrogen bonding http capability (e.g., polyethylene glycol (PEG), cyclodextrin coatings) [1,5]. Wang et al [5] covalently modified the surfaces of polystyrene nanoparticles with CH 3 O-PEG-NH 2 of various molecular weights (MW = 2, 5, 10 kDa) and showed that low PEG MW and high PEG surface coverage are both required for rapid mucus penetration of coated NPs. More specifically, Wang et al [5] observed that there exists a critical MW between 5 and 10 kDa where dense PEG coatings transition from being mucoinert to mucoadhesive.…”
Section: Introductionmentioning
confidence: 99%